A Systematic Review of Whiteness Assessment Properties and Assumptions: Implications for Counselor Training and Research. (2nd January 2023) - Hays, Danica G.; Bayne, Hannah B.; Gay, Jan L.; McNiece, Zachary P.; Park, Cheolwoo
Abstract: The purpose of this article is to present a systematic review of the structural and psychometric properties of 20 Whiteness scales that relate to multiple dimensions of Whiteness (i.e., racism, antiracism, race essentialism, White racial identity, White racial consciousness, colorblind racial ideology, White privilege, psychosocial costs of racism, and White fragility). Furthermore, we identify the frequency of scale use and the 10 underlying theoretical assumptions upon which their development and validation are based. Findings indicate that while many of the underlying assumptions of Whiteness are shared across scales, there is great variation in scale development and validation procedures as well as concerns related to reliability estimates and norming procedures. We provide implications for counselor training and research to maximize the use of these scales as White counselors seek to engage in culturally competent practice.